The Structure of Arabic Reason According to 'Abid Al-Jabiri - Shobirin, Abdurrahman; Yusup, Agung (Indonesian Journal of Islamic Education and Local Culture, 2023)
When Western culture developed with its knowledge and reasoning, many Easterners studied in the West, including Muslims. so that the emergence of Islamic thinkers signaled an epistemological break in the epistemological system of Islamic sciences. The epistemological break has marked and impacted on a paradigm shift in the realm of Islamic thought. The epistemological disconnection in thinking for Arab-Islamic thinkers who explore the development of Western knowledge makes one of the contemporary Arab-Islamic thinkers 'Abid al-Jabiri to create a structure of thinking reason with a deconstructive approach. The reasoning structure consists of bayani, irfani, and burhani reasoning. bayani is the ability of reason to articulate knowledge through signs or symbols into a meaning. 'irfani is the reason to gain knowledge through bathiniyah exercises as often practiced by a Sufi. While burhani is the rationalist reasoning to decide something using the deduction method (istintaj).